y'-xy+x/y =0

i spitted it into

(xy+x/y)dx +dy=0

i tried to solve it by finding integration coefficient

but it gives me

m'+(1-1/y^2)m/(y+1/y)=0

i there any other way

cause i even cant find the integration coefficient

Results 1 to 4 of 4

- Oct 21st 2010, 10:33 AM #1

- Joined
- Nov 2008
- Posts
- 1,401

## y'-xy+x/y =0

y'-xy+x/y =0

i spitted it into

(xy+x/y)dx +dy=0

i tried to solve it by finding integration coefficient

but it gives me

m'+(1-1/y^2)m/(y+1/y)=0

i there any other way

cause i even cant find the integration coefficient

- Oct 21st 2010, 10:35 AM #2

- Oct 21st 2010, 10:45 AM #3

- Oct 21st 2010, 10:47 AM #4